2020
DOI: 10.2174/0929867325666181001104550
|View full text |Cite
|
Sign up to set email alerts
|

A Review: The Anti-inflammatory, Anticancer and Antibacterial Properties of Four Kinds of Licorice Flavonoids Isolated from Licorice

Abstract: : Plants have always been an important source of medicines for humans, and licorice is a very significant herb in the development of humans. As a traditional herb, it is widely cultivated in China, Japan, Russia, Spain and India. With the development of organic chemistry and biochemistry, various chemical ingredients extracted from licorice have been studied and identified. Among them, many chemical components were considered to have strong pharmacological activities, such as anti-inflammatory, anti-ulcer, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…IsoLQ is a flavonoid with anti-inflammatory, antitumoral, and antioxidant properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 16 , 59 ] that exerts protective effects in liver and kidney cells [ 3 , 4 , 9 , 16 , 17 , 18 ]. In addition, it has been demonstrated that IsoLQ does not interfere with CP antineoplastic activity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IsoLQ is a flavonoid with anti-inflammatory, antitumoral, and antioxidant properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 16 , 59 ] that exerts protective effects in liver and kidney cells [ 3 , 4 , 9 , 16 , 17 , 18 ]. In addition, it has been demonstrated that IsoLQ does not interfere with CP antineoplastic activity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its antioxidant activity, it has been reported that IsoLQ scavenges reactive oxygen species (ROS), such as the superoxide anion (O 2 ●− ), hydroxyl radical, hydrogen peroxide, and singlet oxygen [ 4 , 7 ], and induces phase II cytoprotective enzymes’ expression [ 9 , 10 ]. In addition, IsoLQ has been used as an endoplasmic reticulum (ER) stress inducer in cancer cell lines to induce apoptosis [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and also has cytoprotective effects in non-cancer cells, such as liver and kidney cells [ 1 , 4 , 9 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Licorice is an herbal medicine and natural sweetener that is widely used in China and contains numerous active ingredients; its extracts exhibit anti-viral, anti-bacterial, anti-inflammatory, anti-cancer and anti-oxidant activity (56). MgIG is a 4th-generation glycyrrhizic acid agent extracted from licorice by alkali isomerization catalysis; it is currently used as a liver-protecting agent in clinical treatment (57).…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are a group of polyphenolic compounds belonging to the flavonoid class, present in high concentrations in a variety of plant-based fruits, vegetables, and beverages [25,26,27]. Particularly, EC shows protection against dementia, as well as diseases in which oxidative stress seems to be highly prevalent [13].…”
Section: Discussionmentioning
confidence: 99%